Clinico-Pathological Findings of Bangladeshi Covid 19 Patients with their Clinical Outcome: Study of A Cohort of 201 Cases - Ahmed, Nasir Uddin; Islam, Md Azizul; Kabir, Md Anwarul; Rahman, Md Habibur; Sadat, SM Anwar (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: COVID-19 is a major threat to human beings. Clinical characterization, rapid identification of cases and isolation are vital for containments of rapidly spreading disease. The objectives of the study were to evaluate the clinico pathologic profile of Covid 19 positive Bangladeshi patients and also to see their clinical outcome within defined period. Methods: This cohort study on 201 Bangladeshi cases was done in Combined Military Hospital, a tertiary level hospital in Dhaka, Bangladesh from April 2020 to May 2020. Total 201 COVID-19 cases were enrolled after getting the result positive for RT-PCR. After collection, data were analysed to show the characteristics of Covid 19 and their outcome after treatment. Results: Among 201 cases, 180 (90%) were male and 21 (10%) were female. The most prevalent affected age groups were 71 (35.5%) patients in 26-35 years age, 54 (27%) in 16- 25 years, 49 (24.5%) in 35-45 years. Mean age is 32.2±2. Among the total cases, 146 (73%) have positive history of contact, 37 (18.5%) have no history of any contact, 8 (4%) denied any contact with COVID-19 patients. Regarding clinical presentations, 67 (33.5%) patients presented with only one symptoms, 125 (62.5%) had multiple symptoms and 9 (4.5%) cases were asymptomatic. 154 (77%) patients presented with fever. Other presentations were cough 71 (35.5%), headache 27 (13.5%), myalgia 25 (12.5%), sore throat 25 (12.5%), malaise 15 (7.5%), respiratory distress 11 (5.5%). Respiratory system was the dominant domain of clinical presentation. Leukopenia was presented by 12 patients and 12 had lymphopenia. 18 patients had mild thrombocytopenia. Pulse oxymetry showed oxygen saturation below 88% in 12 cases. After oxygen therapy 7 cases were improved and 5 cases were shifted to Corona ICU as their saturation fell below 70. These 5 patients are categorised as severe disease, rest 196 patients were mild in nature. Conclusion: COVID 19 affects male more than female. Common symptoms are fever, cough, headache, myalgia, sore throat, malaise, respiratory distress. Respiratory system is the dominant domain of clinical presentation. ICU support was needed in 2.5 % cases and death rate was 1% which was associated with comorbidity of CKD. J Bangladesh Coll Phys Surg 2020; 38(0): 37-42